Advanced oxygen evolution reaction catalysts for solar-driven photoelectrochemical water splitting. Issue 8 (6th February 2023) - Dong, Guojun; Yan, Lianglin; Bi, Yingpu
Abstract : Herein, we summarize the recent developments in structure optimizations of oxygen evolution reaction catalysts for promoting photoelectrochemical water splitting performances. Abstract : Solar-driven photoelectrochemical (PEC) water splitting is a promising technique for converting abundant solar-energy into clean and sustainable hydrogen fuels. However, the sluggish oxygen evolution reaction (OER) kinetics occurring on semiconductor photoanodes greatly hampered its practical application. To address this issue, the decoration of OER catalysts on photoanode surfaces has been proved to be an effective approach to decrease the reaction overpotential and accelerate the surface OER kinetics, thus improving the PEC performances for water splitting. It was generally recognized that OER catalysts could efficiently extract photo-generated holes from bulk photoanodes to their active sites, so that the surface holes are rapidly consumed in the water oxidation process, effectively restraining charge recombination. Herein, the recent developments in OER catalyst decoration on semiconductor photoanodes for promoting PEC water splitting have been described and discussed. Firstly, the basic principles of PEC water splitting and the functions of OER catalysts have been summarized. Secondly, the structure optimization of OER catalysts, including defect construction, interfacial bonding, elemental doping, morphological regulation and multi-component synergy, toward PEC water oxidation have been discussed. Finally, some challenges and opportunities to achieve further developments in highly efficient OER catalysts for PEC water splitting have been summarized.